1997
DOI: 10.1055/s-0038-1656042
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 (PAI-1) 4G/5G Promoter Polymorphism and Levels in Subjects with Cerebrovascular Disease

Abstract: SummaryThe exact role of the fibrinolytic system in the pathogenesis of stroke remains to be established. Elevated circulating levels of plasminogen activator inhibitor-1, the principle inactivator of the fibrinolytic system, have been related to the development of myocardial infarction. There is evidence that a polymorphism in the promoter region of the PAI-1 gene is associated with circulating PAI-1 levels.We studied a common single nucleotide insertion/deletion (4G/5G) polymorphism by PCR in 558 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 21 publications
8
69
1
1
Order By: Relevance
“…Furthermore, the point estimate of the IRR for the heterozygote individuals was exactly between the IRR estimate for the homozygotes and 1. Together with findings of previous studies, 21 this clearly calls for additional research.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, the point estimate of the IRR for the heterozygote individuals was exactly between the IRR estimate for the homozygotes and 1. Together with findings of previous studies, 21 this clearly calls for additional research.…”
Section: Discussionsupporting
confidence: 64%
“…4,20 The only study on PAI-1 genotype and cerebrovascular disease was suggestive of a reduced risk of stroke incidence for the PAI-1 4G allele compared with the PAI-1 5G allele, although this did not reach statistical significance. 21 Other large studies on PAI-1 4G/5G genotype and stroke have not yet been reported. Additional support for the validity of our findings is provided by the relationship between plasma tPA levels and increased risk of myocardial infarction and stroke, which was consistently found in 4 large studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Moreover, a comparable but nonsignificant reduced stroke incidence in relation to the plasminogen activator inhibitor (PAI-1) 4G polymorphism was reported previously by Catto et al 2 In a pooled analysis of the results of all published studies on the relationship between PAI-1 4G5G genotype and stroke, the genotype distribution in stroke incidence cases is as follows: 4G4G, 296 (26.1%); 4G5G, 559 (49.3%); and 5G5G, 278 (24.5%). The distribution in controls is as follows: 4G4G, 344 (30.1%); 4G5G, 587 (51.3%); and 5G5G, 213 (18.6%).…”
Section: Responsesupporting
confidence: 54%
“…2 The distributions of genotypes in cases were as follows: 4G/4G, 27.1%; 4G/5G, 48.4%; and 5G/5G, 24.5%. The distribution in controls was as follows: 4G/4G, 28.0%; 4G/5G, 53.1%; and 5G/5G, 18.9%.…”
mentioning
confidence: 93%